If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -2a + -1a + -12 = 5a + 5 Reorder the terms: 15 + -12 + -2a + -1a = 5a + 5 Combine like terms: 15 + -12 = 3 3 + -2a + -1a = 5a + 5 Combine like terms: -2a + -1a = -3a 3 + -3a = 5a + 5 Reorder the terms: 3 + -3a = 5 + 5a Solving 3 + -3a = 5 + 5a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5a' to each side of the equation. 3 + -3a + -5a = 5 + 5a + -5a Combine like terms: -3a + -5a = -8a 3 + -8a = 5 + 5a + -5a Combine like terms: 5a + -5a = 0 3 + -8a = 5 + 0 3 + -8a = 5 Add '-3' to each side of the equation. 3 + -3 + -8a = 5 + -3 Combine like terms: 3 + -3 = 0 0 + -8a = 5 + -3 -8a = 5 + -3 Combine like terms: 5 + -3 = 2 -8a = 2 Divide each side by '-8'. a = -0.25 Simplifying a = -0.25
| 1+5t+4=20 | | 3n-1=12 | | 1-5t-4=20 | | x^2-3x-52=0 | | 4x+6=-2x-12 | | x^2+10x-120=0 | | 16t^2+10t-174=0 | | 6x+5=3x+23 | | 1-5t+4=20 | | x-0.60x=644 | | 5x-3x^2= | | v/3=-11 | | 1+3t-4=17 | | -8(x-4)+2=34 | | 1-3t+4=17 | | 2+2t-1=7 | | x-0.40x=18.90 | | -5a^3(4a^4-3a+1)= | | -4r-2(8r-7)=114 | | .75(4x-8)=-10 | | 6x-1=2x+19 | | 2+2t+1=7 | | 174=10t+16t^2 | | 2h^2-28h-98=0 | | 2-2t+1=7 | | 7x+10=4x+4 | | 0=3x^2+36x-39 | | 1+5t-3=19 | | 3(x+4)(x+5)= | | 9x-11=6x+25 | | y=3x^2+36x-39 | | 174=10t+16t |